Linking the Effect of Antibiotics on Partial-Nitritation Biofilters: Performance, Microbial Communities and Microbial Activities - Gonzalez-Martinez, Alejandro; Margareto, Alejandro; Rodriguez-Sanchez, Alejandro; Pesciaroli, Chiara; Diaz-Cruz, Silvia; Barcelo, Damia; Vahala, Riku (Frontiers in Microbiology, 2018)
The emergence and spread of antibiotics resistance in wastewater treatment systems have been pointed as a major environmental health problem. Nevertheless, research about adaptation and antibiotics resistance gain in wastewater treatment systems subjected to antibiotics has not been successfully developed considering bioreactor performance, microbial community dynamics and microbial activity dynamics at the same time. To observe this in autotrophic nitrogen removal systems, a partial-nitritation biofilter was subjected to a continuous loading of antibiotics mix of azithromycin, norfloxacin, trimethoprim and sulfamethoxazole. The effect of the antibiotics mix over the performance, bacterial communities and bacterial activity in the system was evaluated. The addition of antibiotics caused a drop of ammonium oxidation efficiency (from 50% to 5%) and of biomass concentration in the bioreactor, which was coupled to the loss of ammonium oxidizing bacteria Nitrosomonas in the bacterial community from 40% to 3%. Biomass in the partial nitritation biofilter experienced a sharp decrease of about 80% due to antibiotics loading, but the biomass adapted and experienced a growth by stabilization under antibiotics feeding. During the experiment several bacterial genera appeared, such as Alcaligenes, Paracoccus and Acidovorax, clearly dominating the bacterial community with >20% relative abundance. The system reached around 30% ammonium oxidation efficiency after adaptation to antibiotics, but no effluent nitrite was found, suggesting that dominant antibiotics-resistant phylotypes could be involved in nitrification-denitrification metabolisms. The activity of ammonium oxidation measured as amoA and hao gene expression dropped a 98.25% and 99.21%, respectively, comparing the system before and after the addition of antibiotics. On the other hand, denitrifying activity increased as observed by higher expression of nir and nos genes (83.14% and 252.54%, respectively). In addition, heterotrophic nitrification cyt c-551 was active only after the antibiotics addition. Resistance to the antibiotics was presumably given by ermF, carA and msrA for azithromycin, mutations of the gyrA and grlB for norfloxacin, and by sul123 genes for sulfamethoxazole. Joined physicochemical and microbiological characterization of the system were used to investigate the effect of the antibiotics over the bioprocess. Despite the antibiotics resistance, activity of Bacteria decreased while the activity of Archaea and Fungi increased.